Campsis radicans Trumpet Creeper, Trumpet Vine: FPS99/FP099, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the trumpet vine (Campsis radicans), a fast-growing, deciduous vine native to Florida. It details the plant’s characteristics, including its brilliant orange flowers, high drought tolerance, and invasive potential. The trumpet vine thrives in full sun and various soil types but requires regular pruning to manage its growth. It is suitable for arbors, trellises, and containers, attracting hummingbirds and occasionally hosting ants. The document also mentions several cultivars and common issues like leaf spot and powdery mildew. Original publication date October 1999.